Evaluation of 2-thiothiazolidine-4-carboxylic acid, a common metabolite of isothiocyanates as a potential biomarker of cruciferous vegetable intake - Palliyaguru, Dushani L. (Mol Nutr Food Res, 2018)
SCOPE: Cruciferous vegetable consumption is associated with favorable health outcomes. Bioactive compounds arising in these, especially isothiocyanates, exert effects that contribute to prevention of disease, in large part through attenuation of inflammation and oxidative stress. However, much about isothiocyanate metabolites and their role as biomarkers of crucifer intake remain unknown. METHODS AND RESULTS: We tested the utility and limitations of 2-thiothiazolidine-4-carboxylic acid (TTCA) as a urinary biomarker of broccoli beverage intake in a randomized crossover clinical trial where 50 participants consumed either a glucoraphanin-rich (GRR) or sulforaphane-rich (SFR) beverage. Compared to run-in and wash-out periods, we observed significantly higher urinary TTCA after broccoli beverage consumption. Measurements also showed that TTCA was present in beverage powders and in all tested cruciferous vegetables. GRR resulted in excretion of ~87% of the ingested TTCA while SFR resulted in excretion of ~176%. Elevated urinary TTCA was observed in rats administered 100 μmol/kg SFN. Unlike SFN, TTCA did not activate Nrf2-mediated cytoprotective signaling. CONCLUSION: Collectively, TTCA appears to be common isothiocyanate-derived metabolite that has the capacity to be utilized as a biomarker of cruciferous vegetables which would be beneficial for objective and quantitative tracking of intake in studies.